2022
DOI: 10.1371/journal.pone.0264555
|View full text |Cite
|
Sign up to set email alerts
|

Impact of physician’ and pharmacy staff supporting activities in usual care on patients’ statin adherence

Abstract: Aims Little is known about usual care by physicians and pharmacy teams to support adherence to statins and whether the extent of this care is associated with adherence to statins. Objective of the study was to examine the relationship between the extent of adherence supporting activities of healthcare practitioners (HCPs) and patients’ adherence to statins. Methods Cross-sectional study in 48 pharmacies and affiliated physicians’ practices, between September 3, 2014 and March 20, 2015. Patients visiting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Many of the participants in study III reported maximum scores in the medication adherence questionnaire, indicating a ceiling effect. Similar results have been reported in previous studies (175)(176)(177). As described earlier, BMT is an important part of the secondary prevention in patients with IC, and exploring medication adherence is necessary.…”
Section: Methodological Considerationssupporting
confidence: 90%
“…Many of the participants in study III reported maximum scores in the medication adherence questionnaire, indicating a ceiling effect. Similar results have been reported in previous studies (175)(176)(177). As described earlier, BMT is an important part of the secondary prevention in patients with IC, and exploring medication adherence is necessary.…”
Section: Methodological Considerationssupporting
confidence: 90%
“…]24) patients is used in this study as non-adherence is easily underestimated with the MARS [9]. To evaluate sensitivity of the MARS-5 for assessing adherence to DOACs all analyses will be performed for the MARS-5 cut-off scores of <23 and <25 as well [19,20].…”
Section: Self-reported Adherencementioning
confidence: 99%